Kemampuan Powder Activated Carbon dalam Menurunkan Kadar Besi Total pada Air Sumur Bor di Kecamatan Astambul Kabupaten Banjar Tahun 2016 - Sahliah Sahliah; Munawar Raharja; Syarifudin A. (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Powder Activated Carbon Capability In Reducing Total Iron Content In Borehole Well Water In Astambul District Banjar Regency Year 2016. Borehole well water in Astambul Regency is proved containing total iron content with physical characteristics such as the yellow-colored deposits and malodorous smell, then it should be do water processing first, which one alternative is using powder activated carbon. This study aims to find out total iron content in borehole well water after given a treatment by adding powder activated carbon according dose variance and contact time. Dependence variable of this study (total iron content), independence variable (variance and contact time with jar test method). This study is true experimental in nature. The study sample is a resident’s borehole well water in Tambak Danau Village Astambul District Banjar Regency. Data analysis is using Two-Way Anova statistical test. The study results total iron content in borehole well water before processing 3.35 mg/L Fe, after processing the decreasing result to the highest dose variance 0.8 gr/L and contact time 30 minutes results to 0.46 mg/L Fe with declining percentage is 76.64%. The statistical test result in p-value 0.000 < alpha value 0.05. It means, there is a difference in the decrease of total iron content due dose variance and contact time variance. Meanwhile the result of dose*time p-value 0.354 > alpha value 0.05. It means, there is no difference in the decrease of total iron content due to the powder activated carbon dose and contact time variance interaction. Keywords: Total iron content; activated carbon.